Intra-Occupational Gender Earnings Gaps in Malaysia (Jurnal Kemanusiaan, 2017)
ABSTRACT This paper focuses on the gender earnings gap of Malaysian employees within each occupational group. The decomposition method is used to determine the extent to which the intra-occupational gender earnings gaps can be explained by differences in the characteristics of male and female workers. The results show that some part of the earnings gap in the various occupational groups is ascribed to gender differences in education, experience and hours of work whilst a substantial portion of the gap is the residual or discrimination component. Interestingly, the residual or discrimination component of the gender earnings gaps tends to be larger in male-dominated occupations compared to female-dominated and gender-integrated occupations.